Chronobiologic aspects of fetus sex differentiation - S. V. Kalentyeva (Бюллетень сибирской медицины)
The analysis results of 5 213 delivery histories revealed that number of newborn boys was 10 percents more than number of newborn girls. During first pregnancy, conception of boys is more probable in autumn and during the 4-6 months after mother’s birthday. During repetitive pregnancies, conception of boys is more probable in spring and during 3months before mother’s birthday. Conception of boys prevails in young mothers especially in winter and 1-3 months before mother’s birthday. Conception of girls occurs in older women generally more often but conception of boys is more possible in spring and during first 3 months after mother’s birthday.